A systematic review of home-based dietary interventions during radiation therapy for cancer. (December 2020) - Allenby, Taylor H.; Crenshaw, Megan L.; Mathis, Katlynn; Champ, Colin E.; Simone, Nicole L.; Schmitz, Kathryn H.; Tchelebi, Leila T.; Zaorsky, Nicholas G.
Highlights: This is the first systematic review of dietary recommendations for patients receiving radiation therapy. High fiber diet may improve diarrhea in pelvic cancer patients. Limited data to support safe and efficacious use of dietary interventions during radiotherapy. No dietary intervention has been shown to improve survival. Abstract: Purpose: Our objectives are to assess (1) the acceptability and feasibility of dietary interventions for patients undergoing radiation therapy (RT), and (2) the impact of dietary interventions on patient reported outcomes, toxicities, and survival. Methods: A PICOS/PRISMA/MOOSE selection protocol was used to include articles that evaluate adding dietary interventions to patients receiving RT. Acceptability was defined as (# accepting/# approached); feasibility was (# completing/# approached). Patient-reported outcomes were reported based on questionnaires used in each study and survival was measured from the date of diagnosis until death in each study. Level of evidence was assessed with Center for Evidence-Based Medicine (CEBM) criteria. Results: Sixteen articles were included; among these, 2027 patients were approached regarding the intervention, and 1661 accepted (81.9%); of these, 1543 (92.9%) completed the prescribed diet + RT course. The most common cancers included were gynecological, head and neck, and gastrointestinal. For patients with pelvic cancers, a high fiber diet may improve diarrhea (CEBM level 1b). Enteral nutrition formula, including formulas with proteins such as L-arginine, lipids such as eicosapentaenoic acids, glucids, and ribonucleotides, may help prevent of malnutrition in head and neck cancer patients undergoing RT (level 2b). Vitamin C and β-carotene may reduce of xerostomia in head and neck cancer patients; however, the studies evaluating these vitamins included vitamin E, which increases all-cause mortality (level 2b). No dietary intervention for cancer patients receiving RT has been shown to improve survival. Conclusion: There are limited data to support safe and efficacious use of dietary interventions during RT.